Serum DKK-1 level in ankylosing spondylitis: insights from meta-analysis and Mendelian randomization - Fang, Xi; Chen, Cong; Wang, Zhi-Xin; Zhao, Yan; Jiang, Ling-Qiong; Fang, Yang; Zhang, Ruo-Di; Pan, Hai-Feng; Tao, Sha-Sha (Frontiers in Immunology, 2023)
The purpose of this study is to precisely evaluate the serum Dickkopf-1 (DKK-1) level in patients with ankylosing spondylitis (AS) relative to that in normal controls and to test the causal relationship between DKK-1 and the risk of AS.Methods: Embase, PubMed, Web of Science, WANFANG DATA, VIP, and China National Knowledge Infrastructure (CNKI) were comprehensively searched until July 2022 for pertinent studies.The pooled standardized mean difference (SMD) with 95% confidence interval (CI) was calculated by the fixed or random-effect model. In Mendelian randomization (MR) analysis on the causal relationship between serum DKK-1 level and AS risk, the inverse variance weighting method (IVW), MR-Egger regression, weighted median method, and weighted pattern method were applied.Sensitivity analyses, including the horizontal pleiotropy test, heterogeneity test, and leave-one-out test, were also performed.The meta-analysis of 40 studies containing 2 371 AS patients and 1 633 healthy controls showed that there was no significant difference in DKK-1 serum level between AS patients and normal controls (pooled SMD=0.207, 95% CI =−0.418-0.832, P=0.516). The subgroup analysis of the CRP≤ 10 mg/L group showed that AS patients had higher serum DKK-1 concentration than the healthy controls (SMD=2.267, 95% CI = 0.102-4.432, P=0.040). Similarly, MR analysis also demonstrated no significant association between DKK-1 serum level and AS (IVW OR=0.999, 95% CI = 0.989-1.008, P=0.800). All sensitivity analyses revealed consistent results.There is no significant change in serum DKK-1 concentration among AS patients and healthy controls. In addition, no causal relationship exists between serum DKK-1 levels and AS risk.